Predicting Work-Life Conflict: Types and Levels of Enacted and Preferred Work-Nonwork Boundary (In)Congruence and Perceived Boundary Control - Mellner, Christin; Peters, Pascale; Dragt, Maria Johanna; Toivanen, Susanna (Frontiers in Psychology, 2021)
In 2020, everyday life changed dramatically for employees worldwide as a result of the outbreak of the Covid-19 pandemic, where an estimated 558 million employees started working from home. The pandemic, therefore, marks a fundamental shift of individuals’ work-nonwork boundaries, which can impact work-life conflict. In particular, the interplay between individuals’ enacted boundaries (degree to which they separate/segment or blend/integrate work-nonwork), preferred boundaries (degree of preferred segmentation or integration of work-nonwork), and perceived control over work-nonwork boundaries, may relate to work-life conflict. This study, the first to our best knowledge, examines whether different types and levels of work-nonwork boundary (in)congruence matter for work-life conflict, and whether perceived boundary control moderates these relationships. Boundary (in)congruence represents the degree of (mis)fit between enacted and preferred segmentation or integration. Several types of (in)congruence are distinguished: ‘segmentation congruence’ (enacting and preferring segmentation); ‘integration congruence’ (enacting and preferring integration); ‘intrusion’ (enacting integration but preferring segmentation) and ‘distance’ (enacting segmentation but preferring integration). Data from 1,229 managers working in public and private organizations in Sweden was analyzed using polynomial regression analysis with response surface modelling and moderation analysis in SPSS Process. Findings showed that ‘integration congruence’ was related with higher work-life conflict than ‘segmentation congruence’. Moreover, a U-shaped relationship between incongruence and work-life conflict was found: the more incongruence, the more work-life conflict. Specifically, ‘intrusion’ was related to higher work-life conflict than ‘distance’. Finally, boundary control mitigated the effect of incongruence (especially ‘intrusion’) on work-life conflict. From our findings, we may conclude that work-life conflict is impacted differently depending on the type and level of boundary (in)congruence. Particularly enacted and/or preferred integration may be problematic when it comes to work-life conflict, rather than just (in)congruence per se. Moreover, boundary control can be viewed as a key factor in combating work-life conflict, especially among individuals who enact integration, but prefer segmentation. Taken together, our study contributes new and substantial knowledge by showing the importance for research and HRM-policies that take into account different types and levels of boundary (in)congruence, as these are associated with different levels of work-life conflict, which, in turn, are moderated by boundary control.